2012
DOI: 10.1002/uog.11093
|View full text |Cite
|
Sign up to set email alerts
|

Total anomalous pulmonary venous connection: impact of prenatal diagnosis

Abstract: Objectives To investigate whether prenatal screening is effective in the detection of total anomalous pulmonary venous connection (TAPVC) and to identify common prenatal features. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 16 publications
4
98
0
2
Order By: Relevance
“…More recently, Patel et al 28 reviewed their cohort of 13 patients with a prenatal diagnosis of TAPVR over a 13‐year period. The 2 most recent larger series were published by Seale et al 8 from the United Kingdom in 2012 and Laux et al 14 from France in 2013. The former was a multicenter retrospective study reviewing 8 cases of prenatally diagnosed TAPVR, and the latter had 10 cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Patel et al 28 reviewed their cohort of 13 patients with a prenatal diagnosis of TAPVR over a 13‐year period. The 2 most recent larger series were published by Seale et al 8 from the United Kingdom in 2012 and Laux et al 14 from France in 2013. The former was a multicenter retrospective study reviewing 8 cases of prenatally diagnosed TAPVR, and the latter had 10 cases.…”
Section: Discussionmentioning
confidence: 99%
“…However the mid second trimester has only about 15% of the combined ventricular output passing through the lungs, 29 , 30 although this proportion increases to about 25% to 35% of the cardiac output in the third trimester. The small amount of flow return from the lungs early in gestation, with a flow increase only in later gestation, can be a possible reason for inconsistent evidence of a chamber discrepancy before 28 weeks 1 , 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…67 An important risk factor for poor outcome is coexistence of pulmonary vein obstruction, occurring in about 45% of cases and leading to pulmonary venous congestion, pulmonary hypertension, and severe hypoxia soon after birth. 12 68 A more recent study reported that 13% of newborns with obstructed TAPVR were identified prenatally by experienced fetal cardiologists. 12 68 A more recent study reported that 13% of newborns with obstructed TAPVR were identified prenatally by experienced fetal cardiologists.…”
Section: Obstructed Total Abnormal Pulmonary Venous Returnmentioning
confidence: 99%